Controversial Roles of Regenerating Family Proteins in Tissue Repair and Tumor Development - Luting Yu; Qingyun Wu; Shenglong Jiang; Jia Liu; Junli Liu; Guoguang Chen (Biomedicines)
Background: Over the past 40 years since the discovery of regenerating family proteins (Reg proteins), numerous studies have highlighted their biological functions in promoting cell proliferation and resisting cell apoptosis, particularly in the regeneration and repair of pancreatic islets and exocrine glands. Successively, short peptides derived from Reg3δ and Reg3α have been employed in clinical trials, showing favorable therapeutic effects in patients with type I and type II diabetes. However, continued reports have been limited, presumably attributed to the potential side effects. Methods: This review summarizes extensive research on Reg proteins over the past decade, combined with our own related studies, proposing that Reg proteins exhibit dimorphic effects. Results: The activity of Reg proteins is not as simplistic as previously perceived but shows auto-immunogenicity depending on different pathophysiological microenvironments. The immunogenicity of Reg proteins could recruit immune cells leading to an anti-tumor effect. Such functional diversity is correlated with their structural characteristics: the N-terminal region contributes to autoantigenicity, while the C-type lectin fragment near the C-terminal determines the trophic action. It should be noted that B-cell masking antigens might also reside within the C-type lectin domain. Conclusions: Reg proteins have dual functional roles under various physiological and pathological conditions. These theoretical foundations facilitate the subsequent development of diagnostic reagents and therapeutic drugs targeting Reg proteins.